Monitoring Crohn's disease activity: endoscopy, fecal markers and computed tomography enterography. (18th April 2018) - Lopes, Susana; Andrade, Patrícia; Afonso, Joana; Cunha, Rui; Rodrigues-Pinto, Eduardo; Ramos, Isabel; Macedo, Guilherme; Magro, Fernando
Background: The treatment goal of Crohn's disease (CD) has moved towards achieving mucosal healing, resolution of transmural inflammation, and normalization of biomarkers. The purpose of this study was to evaluate how well computed tomography enterography (CTE) and fecal calprotectin (FC) correlated with endoscopic activity in newly diagnosed patients with CD and after 1 year of therapy. Methods: Consecutive patients with newly diagnosed CD were evaluated by endoscopy, CTE, and FC at diagnosis and 12 months after beginning immunosuppression. Endoscopic severity was assessed using the Simplified Endoscopic Score for Crohn's Disease (SES-CD). Biomarkers, clinical indexes, and FC were recorded on the day of ileocolonoscopy at diagnosis and 1 year after diagnosis. We adapted a CTE score for disease activity based on radiological signs of inflammation (i.e. mural thickness, mural hyperenhancement, mesenteric fat proliferation, mesenteric fat densification, comb sign, presence of strictures, fistulas, abscesses, ascites, and lymphadenopathy). Correlations between endoscopy, CTE, and FC were assessed using Spearman's rank correlation. Results: A total of 29 patients (48% women; median age 30 (24.5–35.5) years) were included in this prospective cohort. CTE findings significantly correlated with endoscopic findings. Endoscopic remission (ER) at 1-year follow up significantly correlated with improvement in mural hyperenhancement ( p = 0.004), mesenteric fat densification ( p = 0.001), comb sign ( p = 0.004), and strictures ( p = 0.008) in CTE. None of the CTE findings improved in patients without ER. FC correlated with SES-CD ( rs = 0.696, p < 0.001) and with CTE features of inflammation ( rs = 0.596, p < 0.001). A cut-off of 100 µg/g predicted ER with 92% sensitivity, 65% specificity, and 83% accuracy (area under curve 0.878, p < 0.001). Conclusions: CTE findings and FC levels correlated with endoscopic activity in CD both at diagnosis and at 1-year follow up. These two noninvasive markers of disease activity may be used as an alternative to endoscopy to monitor disease response to therapy.